Warm Phase of AMV Damps ENSO Through Weakened Thermocline Feedback. Issue 23 (7th December 2021) - Trascasa‐Castro, Paloma; Ruprich‐Robert, Yohan; Castruccio, Frederic; Maycock, Amanda C.
Abstract: Interactions between ocean basins affect El Niño–Southern Oscillation (ENSO), altering its impacts on society. Here, we explore the effect of Atlantic Multidecadal Variability (AMV) on ENSO behavior using idealized experiments performed with the NCAR‐CESM1 model. Comparing warm (AMV+) to cold (AMV−) AMV conditions, we find that ENSO sea surface temperature (SST) anomalies are reduced by ∼10% and ENSO precipitation anomalies are shifted to the west during El Niño and east during La Niña. Using the Bjerknes stability index, we attribute the reduction in ENSO variability to a weakened thermocline feedback in boreal autumn. In AMV+, the Walker circulation and trade winds strengthen over the tropical Pacific, increasing the background zonal SST gradient. The background changes shift ENSO anomalies westwards, with wind stress anomalies more confined to the west. We suggest the changes in ENSO‐wind stress decrease the strength of the thermocline feedback in the east, eventually reducing ENSO growth rate. Plain Language Summary: El Niño–Southern Oscillation (ENSO) is the dominant mode of year‐to‐year climate variability in the tropics and affects regional climates around the world. Understanding the drivers of ENSO behavior is important for its prediction. One influential factor is communication between ocean basins, such as the North Atlantic interaction with the tropical Pacific. In our work, we use idealized simulations that represent the positive and negative phases of the Atlantic Multidecadal Variability (AMV) to understand how sea surface temperature changes in the North Atlantic affect the dynamics of ENSO in the tropical Pacific. We find that both El Niño and La Niña events are weaker when the North Atlantic is warmer than usual, and vice versa. During the warm phase of the AMV (AMV+), the trade winds associated with the Walker circulation are localized in the west Pacific, directly impacting sea surface temperature patterns associated with ENSO events. Reduced wind stress in the eastern equatorial Pacific means that the upper ocean heat content is less perturbed in the AMV+ simulation, eventually feeding back to ENSO‐related sea surface temperatures. Key Points: AMV weakens ENSO sea surface temperature anomalies by 10% and local ENSO precipitation anomalies by up to 45% The thermocline feedback in the tropical Pacific is weakened in boreal autumn, reducing ENSO growth rate AMV causes changes in the Pacific mean state that lead to wind stress anomalies being more confined in the west Pacific during ENSO onset